Episodic memory meets working memory in the frontal lobe: functional neuroimaging studies of encoding and retrieval. - Lee, A; Robbins, T; Owen, A (2000)
Recent functional-neuroimaging studies have provided a wealth of new information suggesting that regions of the prefrontal cortex play a role in episodic memory encoding and retrieval. This review seeks to evaluate the results of these studies in the context of one general model that has proposed that the left prefrontal cortex is preferentially involved in episodic memory encoding, whereas the right prefrontal cortex is preferentially involved in episodic memory retrieval, irrespective of the type (e.g., modality) of information being remembered. The origins of this framework are considered in some detail and then all relevant functional-neuroimaging studies are critically reviewed. The results of this review fail to provide support for the functional-asymmetry model, suggesting instead that episodic memory encoding and retrieval may actually involve similar regions of the lateral prefrontal cortex when all factors relating to the type of stimulus material (i.e., modality), are appropriately controlled.